A practical analytical model for predicting the low-velocity impact response of 3D-fiber metal laminates - Asaee, Zohreh; Taheri, Farid (Mechanics of advanced materials and structures, 2020)
The main objective of present study is to develop a practical analytical model for predicting the static (indentation) and low-velocity impact responses of 3D fiber metal laminates (3DFML). An energy balance approach is used, by which the impact induced energy into various configurations of 3DFML is assumed to dissipate through shear, bending and indentation contact mechanisms. The indentation contact is formulated using the Hertz law. The contact parameters are calculated for various configurations of 3DFML. The variation in the contact parameters as a function of 3DFML configuration and the indentation area is investigated. The developed analytical model is generalized and modified based on the configurations of 3DFMLs and impactor's geometry. The integrity of the proposed analytical model is verified by comparison of its results against results obtained through experiments and numerical simulations. The numerical simulations are performed using commercial finite element software ABAQUS/Explicit. Comparison of the results indicates that the proposed model can reliably predict the maximum impact force and deformation of the 3DFMLs, up to the stage at which a crack develops on the 3DFML.